2022
DOI: 10.1111/jam.15464
|View full text |Cite
|
Sign up to set email alerts
|

Ambient pH regulates lactate catabolism pathway of the ruminal Megasphaera elsdenii BE2-2083 and Selenomonas ruminantium HD4

Abstract: Aims:To explore the impact of ambient pH on lactate catabolism by Megasphaera elsdenii BE2-2083 and Selenomonas ruminantium HD4 in both pure culture and in binary mixed culture. Methods and results:The growth rate, substrate consumption, product formation, enzymatic activity and gene expression of M. elsdenii and S. ruminantium at various pHs were examined. Furthermore, the metabolism of lactate catabolism pathways for M. elsdenii and S. ruminantium in the co-culture system was investigated by chasing the conv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 46 publications
1
1
0
Order By: Relevance
“…lactilytica ). These results are supported by the more recent work of Fan et al [ 94 ] who used 13 C-NMR to show that in batch-mode binary co-cultures with S. ruminantium subsp. lactilytica , M. elsdenii accounted for 82% and 75% of 13 C-D-lactate catabolism at pH 6.5 and 5.5, respectively.…”
Section: Relationships With Others Ruminal Microorganismssupporting
confidence: 76%
See 1 more Smart Citation
“…lactilytica ). These results are supported by the more recent work of Fan et al [ 94 ] who used 13 C-NMR to show that in batch-mode binary co-cultures with S. ruminantium subsp. lactilytica , M. elsdenii accounted for 82% and 75% of 13 C-D-lactate catabolism at pH 6.5 and 5.5, respectively.…”
Section: Relationships With Others Ruminal Microorganismssupporting
confidence: 76%
“…lactiltyica did (5.49 × 10 −14 mol cell −1 h −1 versus 2.42 × 10 −14 mol cell −1 h −1 ). Moreover, Fan et al [ 94 ] reported that, on lactate, M.elsdenii BE2-2083 displayed higher maximum specific growth rates than Selenomonas ruminantium subsp. lactilytica HD4 did at both pH 6.5 and pH 5.5 as well as shorter lag times before initiating growth.…”
Section: Relationships With Others Ruminal Microorganismsmentioning
confidence: 99%
“…lactilytica). These results are supported by the more recent work of Fan et al [94] who used 13 C-NMR to show that in batch-mode binary co-cultures with S. ruminantium subsp. lactilytica, M. elsdenii accounted for 82% and 75% of 13 C-D-lactate catabolism at pH 6.5 and 5.5, respectively.…”
Section: Relationships With Others Ruminal Microorganismssupporting
confidence: 75%
“…Additionally, while bovine lactate-utilizing bacteria proliferated during corn fermentations, ovine lactate-utilizing bacteria remained at initial baseline levels, resulting in a 1000-fold difference between species at 24 h. Given that ruminal bacteria from sheep were able to produce the same amount of VFA without the need for proliferation of lactateutilizers, this indicates the resident lactate-utilizing guild of sheep may have superior energetic end-product production efficiency from high-starch diets in comparison with cattle. Multiple pathways contribute to lactate catabolism in the rumen [59], and efficiencies differ across members of the lactate-utilizing guild [60]. Lactate-utilizing bacteria were not isolated in the current study; therefore, these findings merit additional investigation to evaluate potential compositional and functional differences in lactate-utilizing bacteria between cattle and sheep.…”
Section: Discussionmentioning
confidence: 78%